Immunology of stiff person syndrome and other GAD-associated neurological disorders. (November 2013) - Alexopoulos, Harry; Dalakas, Marinos C
Antibodies against glutamic acid decarboxylase (GAD), the rate-limiting enzyme for the synthesis of GABA, are associated with an array of distinct, mostly autoimmune, neurological conditions. In all associated syndromes, namely stiff person syndrome, cerebellar ataxia, epilepsy, limbic encephalitis or abnormal eye movements, anti-GAD antibodies are detected at high titers and play a fundamental role in diagnosis, but do not correlate with disease severity, diversity of symptomatology or response to therapies. Despite considerable efforts, including in vitro (enzymatic assays) and in vivo (animal models) systems, the pathogenicity of anti-GAD antibodies has not been unequivocally proven for any specific condition. The search for the responsible autoantigen has revealed a few other antigenic targets, particularly for SPS, localized in the pre- or post-synaptic inhibitory neuronal synapses. Cumulative clinical and laboratory evidence indicates that anti-GAD and related antibodies define a novel group of syndromes, collectively known as 'hyperexcitability disorders'.